Optimasi Sistem Transformasi Gen Xiloglukanase Pada Eucalyptus pellita F. Muell Menggunakan Agrobacterium tumefaciens - Sri Hartati; Andriyani Puspitaningrum; Nita Etikawati; Enny Sudarmonowati (Bioscience, 2018)
Eucalyptus pellita is a type of woody plant that is widely used as raw materials of pulp and paper so that the need for wood from this type of plant is increasing. Improvements in wood quality such as cellulose deposition and increased growth rates are needed to support the supply of raw materials for the pulp and paper industry. One technology to change the composition of wood is the modification of plant cell walls through the transformation of xylolukanase gene which in other plants such as Populus alba and Acacia mangium have been shown to increase cellulose deposition and spur growth. The purpose of this study was to obtain an efficient xyloglucanase transformation method in E. pellita using Agrobacterium tumefaciens. Sprouts E. pellita 006 and 06A with different ages of 8 and 15 days are used as plant material for transformation. The sonication treatment of the sprouts prior to the transformation was also applied to determine the effect on transformation efficiency. Transformation is done by soaking the seeds that have been through the treatment of sonication and without sonication on the suspension of Agrobacterium carrying plasmid pAa XEG300 and subsequently grown on the selection medium. Sprouts E. pellita 006 aged 15 days without sonication treatment showed the highest percentage of regeneration in the selection media that is equal to 72%. Gene integration testing through DNA amplification with specific primers showed a ribbon of xyloglucanase with a size of 709 bp.